Effects of donor plant age and explants on in vitro culture of Cedrela montana Moritz ex Turcz - Basto, Sofia; Departamento de Biología Facultad de Ciencias Pontificia Universidad Javeriana (2012)
Abstract. To evaluate the organogenic potential of Cedrela montana Moritz ex Turcz. Explants from mature (10-20 year-old) and juvenile (7-18 month-old) trees were collected. The first grouping included buds, leaves, and nodes derived from juvenile basal offshoots and rejuvenated shoots from cuttings. The second, included leaves, petioles, nodes, internodes and nodes of in vitro elongated shoots. The highest organogenic potential was observed in nodes from juvenile trees: 45.8% of explants presented axillary bud elongation, while 56.2% presented rooting in a growth regulator free culture medium. Fifty-one percent of elongated shoots produced adventitious shoots with 0.5 μM NAA and 0.5 μM BA; 30% with 0.5 μM NAA and 1 μM BA; and 30% with 1 μM BA. Twenty percent presented roots with 0.5 μM NAA. Root formation was stimulated in a medium supplemented with activated charcoal (5 gL-1). The acclimatization of eighty percent of plantlets regenerated from nodes, and of 72.5% in vitro generated shoots was successful. On the contrary, mature trees material presented low organogenic response. Axillary bud elongation was recorded just in 10.7% of explants from juvenile shoots and in 6.7% of explants from rejuvenated shoots. The age of donor plant and type of explant affect the organogenic potential of C. montana. This study contributes to the understanding of this species’ response under in vitro conditions.